Keratinase Activity of Some Hyphomycetous Fungi from Dropped Off Chicken Feathers - Awasthi, Prerna (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT In this study identified hyphomycetous fungi isolated from dropped off chicken feathers, showed keratinolytic ability by making a clear zone around their colonies on SMA medium. Among 101 keratinolytic hyphomycetous fungi, 13 species belonging to six genera examined for keratinase activity in submerged cultures using chicken feather as keratinous substrate. The highest keratinolytic activities were recorded in Acremonium brunnescens MTCC 10376, (65.73± ku/ml), Chrysosporium indicum MTCC 10377 (63.5±2.47 ku/ml), Acremonium chrysogenum NFCCI 1883 (45.11±1.59 ku/ml), Acremonium byssoides MTCC 9985 (41.66±0.75 ku/ml), Scopulariopsis stercoraria NFCCI 1885 (34.6±3.69 ku/ml) Chrysosporium tropicum NFCCI 1884 (24.69±2.11 ku/ml), Fusarium culmorum GPCK 3204 (22.91±0.86 ku/ml) and Alternaria alternata NFCCI 1878 (20.8±3.69). These noval nondermatophytic keratinolytic fungi have potential use in biotechnological processes involving keratin hydrolysis. The result of this work contributes to show that keratinolytic activity is relatively widespread among common hyphomycetous fungi and may have an important role in feather degradation in natural environment.